Emotional Intelligence Training Program and its Effect on Nursing Students Problem Solving Skills - Sabah Mohamed Ragab; Mona Mostafa Shazly; Hemat Abdel-Azeem Mostafa (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Emotional intelligence is comprised of individual, emotional, and social abilities. Itincludes the competency of an individual to manage their relationships with others, and regulate emotionsand efficiently solved their problem. Aim: this study aims to assess the effect of emotional intelligencetraining program on nursing students problem solving skills. Design: A pretest- posttest one group quasiexperimentalstudy design was used. Setting: The study was conducted at the Technical Nursing Instituteat El-Fayoum University. Subjects: included all the available nursing students at second year was 200nursing students. Tools of data collection: Data were collected by using two tools emotional intelligencequestionnaire and problem solving skills questionnaire. Results: 48.5% of the nursing students had highemotional intelligence before the intervention. This increased to 86.5% at the post intervention phase and theimprovement continued through the follow up phases reachingto89.5%. Half of nursing students in the studysample were high problem solving skills before the intervention. This rose to 87.5% at the post interventionphase and reached 90.5% at the follow-up phase. Conclusion: There were highly statistically significantcorrelations between emotional intelligence and problem solving skills. Recommendations: The TechnicalInstitute of Nursing should adopt the emotional intelligence, educational approach in all its different gradesand Enhance nursing problem solving skills through providing them with supportive and positive trainingenvironment.